Evaluating Whole-Page Relevance - Bailey, Peter; Craswell, Nick; White, Ryen W.; Chen, Liwei; Satyanarayana, Ashwin; Tahaghoghi, S.M.M. (33rd Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2010), Geneva, Switzerland, 2010)
Whole page relevance defines how well the surface-level representation of all elements on a search result page and the corresponding holistic attributes of the presentation respond to users’ information needs. We introduce a method for evaluating the whole-page relevance of Web search engine results pages. Our key contribution is that the method allows us to investigate aspects of component relevance that are difficult or impossible to judge in isolation. Such aspects include component-level information redundancy and cross-component coherence. The method we describe complements traditional document relevance measurement, affords comparative relevance assessment across multiple search engines, and facilitates the study of important factors such as brand presentation effects and component-level quality.